Principles of Administrative Law : A Comparative Study - Hamid Khan (Karachi Oxford University Press, 2020)
Administrative Law is a key subject in the field of public law and forms an essential study for lawyers, judges, law students, law teachers, and administrators.
Include Bibliography and Index
Keywords: Administrative law -- United States -- Pakistan